Hubungan Indeks Masa Tubuh (IMT) dengan Persen Lemak Tubuh, dan Lemak Viscelar di Kota Semarang - Susantini, Purwanti (Universitas Muhammadiyah Semarang, 2021)
Indonesia is predicted to experience a demographic bonus period, namely the number of productive age population (aged 15-64 years) of 64%. The prevalence of obesity at productive age from 2007 to 2018 has increased from 8.6% to 13.6%. Obesity will result in high percent body fat andvisellar fat, and will result in various non-communicable diseases such as type 2 diabetes, cardiovascular disease, stroke, cancer and other non-metabolic complications such as arthritis. The onset of this disease in obese people is preceded by a group of symptoms such as hypertension, insulinresistance, dyslipidemia. Objectives: To determine the relationship between Body Mass Index and Percent body fat and to determine the relationship between Body Mass Index and Viscelar Fat. Methods: This study used a cross sectional design with purposive sampling method, namely thosevisiting the Aisyiyah Regional Leadership Stand in Semarang City at the Expo of Community Organizations in Semarang City. The sample is 115 people. Results: This study found that 35 (30.4%) men and 80 (69.6%) women, Average Age: (45.14 ± 14.55) years, Body Mass Index (25.39 ± 3.96), mean percent body fat (32.63 ± 6.68) mean viscelar fat (7.93 ± 5.13). There is a relationship between BMI and percent body fat (p = 0.000) and there is a relationship between BMI and Viscelar fat (p = 0.000).Keywords: Body Mass Index, percent body fat, Viscelar fat